Message transmission efficiency through five telecommunication technologies for signing deaf users. - Vincent C; Bergeron F; Hotton M; Deaudelin I (Assistive Technology)
Recent reports in the rehabilitation literature have suggested that treatment theory, intervention specification, and treatment fidelity have important implications for the design, results, and interpretation of outcomes research. At the same time, there has been relatively little discussion of how these concepts bear on the quality of assistive technology (AT) outcomes research. This article describes treatment theory, intervention specification, and treatment fidelity as interconnected facets of AT outcome studies that fundamentally affect the interpretation of their findings. The discussion of each is elucidated using case examples drawn from the AT outcomes research literature. Recommendations are offered for strengthening these components of AT outcomes research.